Your own, Sylvia a verse portrait of Sylvia Plath - Hemphill, Stephanie (New York Alfred A. Knopf, 2007)
The author interprets the people, events, influences and art that made up the brief life of Sylvia Plath.
Keywords: Plath, Sylvia -- Juvenile poetry